Graphene Nanoplatelets (GnP)-PVA Based Passive Saturable Absorber - Nabihah Hussin; Mohd Haniff Ibrahim; Fauzan Ahmad; Hafizal Yahaya; Sulaiman Wadi Harun (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A passive Q-switched pulsed laser at 1.5 m region incorporating graphene nanoplatelets (GnPs) embedded in Polyvinyl Alcohol (PVA) is demonstrated. A surfactant is used to aid the dispersion of the GnPs before it is mixed with PVA to develop a GnPs-PVA film based SA. The SA is integrated into the laser cavity by attaching a cut of the GnPs-PVA film in between two fiber ferrule of the laser ring cavity.The proposed GnPs-PVA film based passive Q–switched laser was able to operate as the input pump power was increased from 39 mW up to a maximum of 148 mW before diminishing. The laser obtained operated with a central wavelength of 1530.76 nm. Repetition rates were obtained at 33 kHz to 91.5 kHz, throughout the tunable input pump power with the shortest pulse width of 2.42 s. Maximum attainable peak power and pulse energy of 1.2 mW and 5.9 nJ, respectively, was recorded, accompanied by a signal to noise ratio (SNR) of 28 dB.